Photogrammetric digitisation of a bronze head – Surveying inside and outside for thickness measurement - L. Perfetti; G. P. M. Vassena; F. Morandini; F. Fassi (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This paper presents an effective and low-cost approach for the digitisation of a Roman bronze head exhibited at the Santa Giulia Museum in Brescia using close-range photogrammetry. The artefact posed significant challenges due to its dark, reflective exterior surface and its hollow interior, accessible only through an 8 cm neck opening. The digitisation had two main objectives: (1) to support restoration activities by accurately measuring the thickness of the bronze cast, and (2) to enhance the artefact's dissemination by producing a web-optimised digital replica. Special emphasis was placed on the survey of the internal surface, achieved using a custom-designed camera probe equipped with a 5 megapixels RGB global shutter camera and LED ring lights. With this setup it was possible to effectively captured the inner geometry using low-cost tools. The internal dataset was connected with the exterior dataset, acquired by a regular DSLR and turntable setup supported by cross-polarization. The processing workflow involved generating a high-resolution mesh model (~80M faces) and computing the cast's thickness using two methods: the M3C2 algorithm and the Shrinking Sphere algorithm, which provided consistent results. Additionally, an optimised low-poly version of the model was created for web sharing. This study highlights the potential of low-cost tailored photogrammetric solutions/workflows to address the complexities of digitising intricate museum artefacts.